From the Margins of the Media to the Margins of Intermediality Studies (KULT_online, 2016)
Intermediality serves as an umbrella-term that describes the manifold and complex relationships between the arts and their media. And as broad as the term itself is, so diverse and heterogeneous are the described phenomena. The Handbook of Intermediality. Literature - Image - Sound - Music collects more than 30 articles opening new perspectives on current questions around Intermediality, its theories, methods, and corresponding case studies. From different perspectives and fields the texts not only point to the medial boundaries, but also question the boundaries and limitations of the intermediality studies themselves.